Pengaruh penggunaan media sosial dan teman sebaya terhadap prestasi belajar mahasiswa dimediasi motivasi - Muhammad Askuri Nur Rochman; Muhammad Sabandi; Dini Octoria (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to determine the effect of the use of social media and peers on learning achievement mediated by motivation in economics students at the Faculty of Teacher Training and Education, Sebelas Maret University. The type of research used is quantitative with a survey method and the sample used is 262 economics students. The validity test used in this study uses Connfirmatory Factor Analysis (CFA) and uses the Cronbach Alpha reliability test. The data analysis technique used in this study is hierarchical regression analysis. Based on the results of the study, it is concluded that 1) there is a positive and significant influence between the variables of social media use on learning motivation, 2) peer variables directly do not influence learning motivation, 3) motivation variables do not influence learning achievement, 4) there is a significant influence between the variables of social media use on learning achievement, 5) there is a significant influence between peer variables on learning achievement.